Can magnetic fields suppress convection in the atmosphere of cool white dwarfs?: a case study on WD2105−820 - Gentile Fusillo, Nicola Pietro; Tremblay, Pier-Emmanuel; Jordan, Stefan (Monthly notices of the Royal Astronomical Society, 2018)
Around 10 per cent of white dwarfs exhibit global magnetic structures with fields ranging from 1 kG to hundreds of MG. Recently, the first radiation magnetohydrodynamics simulations of the atmosphere of white dwarfs showed that convection should be suppressed in their photospheres for magnetic fields with strengths B ≳ 50 kG. These predictions are in agreement with our knowledge of stellar physics (e.g. energy transfer in strong magnetic field regions of the solar photosphere), but have yet to be directly confirmed from white dwarf observations. We obtained Cosmic Origins Spectrograph (COS) far-ultraviolet (FUV) spectroscopy of the weakly magnetic, hydrogen-atmosphere, white dwarf WD2105−820 and of three additional non-magnetic, convective remnants (all in the Teff range 9000-11 000 K). We fitted both the COS and the already available optical spectra with convective and radiative atmospheric models. As expected, we find that for two of the non-magnetic comparison stars only convective model fits predicted consistent Teff values from both the optical and the FUV spectra. In contrast, for WD2105−820 only the best-fitting radiative model produced consistent results.